High-Resolution Numerical Modeling of Barotropic Global Ocean Tides for Satellite Gravimetry - Sulzbach, R.; Dobslaw, H.; Thomas, M. (Journal of Geophysical Research: Oceans, 2021)
The recently upgraded barotropic tidal model TiME is employed to study the influence of fundamental tidal processes, the chosen model resolution, and the bathymetric map on the achievable model accuracy, exemplary for the M-2 tide. Additionally, the newly introduced pole-rotation scheme allows to estimate the model's inherent precision (open ocean rms: 0.90 cm) and enables studies of the Arctic domain without numerical deviations originating from pole cap handling. We find that the smallest open ocean rms with respect to the FES14-atlas (3.39 cm) is obtained when tidal dissipation is carried out to similar parts by quadratic bottom friction, wave drag, and parametrized eddy-viscosity. This setting proves versatile to obtaining high accuracy values for a diverse ensemble of additional partial tides. Using the preferred model settings, we show that for certain minor tides it is possible to obtain solutions that are more accurate than results derived with admittance assumptions from data-constrained tidal atlases. As linear admittance derived minor tides are routinely used for de-aliasing of satellite gravimetric data, this opens the potential for improving gravity field products by employing the solutions from TiME. Plain Language Summary We introduce the upgraded computer model TiME, that simulates ocean tides originating from the gravitational attraction of the sun and moon. The model relies on the physics of relevant processes without incorporating actual observations of water level variations. Formerly unconsidered effects that strongly impact tidal dynamics are now included. We discuss the individual impact of these effects on the model accuracy, which is estimated relatively to local measurements from tide gauges. We further compare our results to external tidal models, that employ satellite observations for increased accuracy. Here we find that the upgraded model performs well in the open ocean, and has a reduced accuracy in shallow and coastal waters. The final model setting can simulate tides that recur ...